(untitled) (Global Journal of Human-Social Science, 2021)
The Indian economy is dualistic It consists of both sectors one is well organized and another is unorganized informal sector The informal sector is dominated by self-employed persons Employment in the informal sector is uncertain The workers in the informal sector have no access to social security wage protection and a decent wage To address the issue of decent jobs the government of India tried to focus on the social protection and enforcement of the wage legislation Article 43 of the Constitution states that The state shall endeavor to secure by suitable legislation or economic organization or in any other way to all workers agricultural industrial or otherwise work a living wage conditions of work ensuring a decent standard of life and full enjoyment of leisure and social and cultural opportunities in particular 1 Article 39 of the Constitution states that the State shall in particular direct its policy towards securing a that the citizen men and women equally shall have the right to an adequate livelihood and b that there is equal pay for equal work for both men and women 2 In the light of the abovementioned articles of the Constitution the paper is an attempt to analyzing the code on wages 2019 and its provisions